Sistemas monetarios alternativos - Hadba, Fernando Antonio (1994)
This paper is a collection of surveys about alternative monetary systems. It hegins with metalic anda comondity monetary systems. Keeping this line of evolution, the next step is the study of 100% covered emissions like the currency boards and the extreme of the abolition of no national money. The last article concerns the Hayek of the desnationalization of money.